Plain Meaning and Linguistics—A Case Study - Michael S. Moore (Washington University Law Quarterly, 1995)
Semantics is the locus of a potentially fruitful co-operation between linguists and lawyers. Yet one of the pervasive dangers in interdisciplinary work is that the urge to integrate the insights of one discipline with the tasks of another often causes a warping of the latter in order to make it more receptive to the proposed integration. Such I fear is the case with the linguistics expertise proffered to the United States Supreme Court recently, via an amicus brief by the Law and Linguistics Consortium.
Keywords: Linguistics; Law -- Interpretation & construction; Legal language